2011
DOI: 10.1103/physrevb.84.054539
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic magnetic pinning and reversible resistance switching in high-temperature superconductor/ferromagnet multilayers

Abstract: We study a high-critical temperature superconducting (YBa 2 Cu 3 O 7-δ )/ferromagnetic (Co/Pt multilayer) hybrid that exhibits resistance switching driven by the magnetic history: depending on the direction of the external field, a pronounced decrease or increase of the mixed-state resistance is observed as magnetization reversal occurs within the Co/Pt multilayer. We demonstrate that stray magnetic fields cause these effects via (i) creation of vortices/antivortices and (ii) magnetostatic pinning of vortices … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…A model confining potential may be realized in the planar superconductor(S)/ferromagnet(F) bilayer (SFB), in which the magnetic domains in the F layer create pinning potential for vortices 6,[11][12][13][14][15][16][17][18][19][20] . When the F layer exhibits perpendicular magnetic anisotropy (PMA) with a welldefined direction of the magnetic moment of the domain, the vortices are selectively attracted to the domains of one sign [21][22][23][24][25][26][27][28][29][30][31][32] . Recently, several experiments demonstrated formation of single or multiple vortex chains confined to domains of one sign in SFB's with stripe domain patterns, in which equal amount of +/− domains exist.…”
Section: Introductionmentioning
confidence: 99%
“…A model confining potential may be realized in the planar superconductor(S)/ferromagnet(F) bilayer (SFB), in which the magnetic domains in the F layer create pinning potential for vortices 6,[11][12][13][14][15][16][17][18][19][20] . When the F layer exhibits perpendicular magnetic anisotropy (PMA) with a welldefined direction of the magnetic moment of the domain, the vortices are selectively attracted to the domains of one sign [21][22][23][24][25][26][27][28][29][30][31][32] . Recently, several experiments demonstrated formation of single or multiple vortex chains confined to domains of one sign in SFB's with stripe domain patterns, in which equal amount of +/− domains exist.…”
Section: Introductionmentioning
confidence: 99%
“…As previously suggested, the magnetic domains in the F layer create pinning centers for the vortices in the S layer so that tuning the domain structure can result in tuning J c 4,5 . While the principle of magnetic pinning in the SFB's has been extensively discussed theoretically [2][3][4][5][6][7][8][9][10][11] and demonstrated experimentally [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , the magnitude of the pinning enhancement thus far reported has been modest with a factor of no more than 3, and sometimes even suppression of pinning has been described 18 . Furthermore, it has not been feasible to compare various magnetic pinning results, since the different SFB bilayers used in these studies would render such comparison impractical.…”
mentioning
confidence: 99%
“…I, changes in the superconductor critical current, anisotropy, and mixed state resistance depending on the magnetization of the ferromagnet have been reported. [37][38][39][40][41] Song et al have reported that, in parallel field, the hysteretic magnetization curves of the superconducting film included in a coated conductor deposited on a magnetic substrate present features very different from the classical shape obtained with CCs deposited on a nonmagnetic substrate. 22 This confirms that the presence of the ferromagnet has a strong influence on the vortex population in the superconductor.…”
Section: Discussionmentioning
confidence: 95%